Indirect method for quantifying the content of photosynthetic pigments in genotypes of dwarf elephant grass - doi: 10.4025/actascianimsci.v35i1.15178 (Acta Scientiarum. Animal Sciences, 2012)
Equations that indirectly associate the rates obtained by chlorophyll meter SPAD-502 to chlorophyll and carotenoids rates of dwarf elephant grass genotype are provided. Leaves of the genotype of dwarf elephant grass were employed. After being collected, they were transported in light-protected styrofoam boxes to the Plant Physiology Laboratory of UENF. Leaf discs of the known area were then extracted. An average of 5 readings/leaf disc were undertaken by portable chlorophyll meter SPAD-502, with 6 discs for each range and distributed according to the following scale: 0-10; 10-20; 20-30; 30-40; 40-50; 50-60. Chlorophyll meter SPAD-502 provides a quick and efficient estimate of total chlorophyll, chlorophyll-a and chlorophyll-b in genotypes of dwarf elephant grass.